Impact of OTAs’ Digital Services on Customer Satisfaction in Thailand - Pholkerd, Panjamapon; Thamnarong, Mallika; Nittayakamolphun, Pitipat (Journal of Applied Economics and Management Strategy, 2024)
The availability of digital technology has prompted many adaptations in the hotel industry, particularly among online travel agents (OTAs). Better services provided by OTAs might improve customer satisfaction. This research aims to examines the effect of OTAs’ Digital Services (DS), electronic service quality (ESQ), and electronic recovery service quality (ERSQ) on consumer satisfaction (CSAT). To better understand customer satisfaction via online booking, research survey of 415 persons in Thailand who have used OTAs to book hotels was conducted. For data analysis, structural equation modeling (SEM) was used. The study covers the metrics and conditions that could lead to consumer satisfaction. According to the study's findings, ESQ and ERSQ are the factors that would directly affect consumer satisfaction while DS can rather effect consumer satisfaction indirectly. Based on the findings, OTAs service providers should enforce quality and simplicity on their platforms, such as swift booking transactions, precise booking detail, and booking experience when searching for rooms. Customer satisfaction would progressively spread information, lowering marketing costs while increasing reliability.